2004
DOI: 10.1152/classicessays.00004.2004
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypoxia and pulmonary vasoconstriction in humans: uncovering the mechanism of the pressor response

Abstract: This essay looks at the historical significance of an APS classic paper that is freely available online:Motley HL, Cournand A, Werko L, Himmelstein A, and Dresdale D. The influence of short periods of induced acute anoxia upon pulmonary artery pressures in man. Am J Physiol 150: 315-320, 1947 (http://ajplegacy.physiology.org/cgi/ reprint/150/2/315).FOR THE LUNGS TO OPERATE EFFICIENTLY in gas exchange, it is essential for the pulmonary blood flow to be directed to well-ventilated areas of the lungs. Teleologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…At high altitude, the entire lung is unavoidably exposed to lowered inspired oxygen. An immediate reaction is the hypoxic pulmonary vasoconstriction reflex, measured as an increase in pulmonary artery blood pressure, that “automatically increases pulmonary vascular resistance in poorly aerated regions of the lungs, thereby redirecting pulmonary blood flow to regions richer in oxygen content” (Fishman,2004 p. L893). Lifelong exposure would predict unrelieved hypoxic pulmonary vasoconstriction and lead to sustained elevated pulmonary artery pressure and vascular resistance that could progress to cardiac enlargement (cor pulmonale) or right heart failure.…”
mentioning
confidence: 99%
“…At high altitude, the entire lung is unavoidably exposed to lowered inspired oxygen. An immediate reaction is the hypoxic pulmonary vasoconstriction reflex, measured as an increase in pulmonary artery blood pressure, that “automatically increases pulmonary vascular resistance in poorly aerated regions of the lungs, thereby redirecting pulmonary blood flow to regions richer in oxygen content” (Fishman,2004 p. L893). Lifelong exposure would predict unrelieved hypoxic pulmonary vasoconstriction and lead to sustained elevated pulmonary artery pressure and vascular resistance that could progress to cardiac enlargement (cor pulmonale) or right heart failure.…”
mentioning
confidence: 99%
“…The pulmonary baroreceptors may also be of importance during exposure to hypoxic stress. For example, pulmonary hypertension is known to develop in unacclimatized healthy individuals exposed to high altitude; this is due to vasoconstriction of small muscular resistance pulmonary arteries in response to alveolar hypoxia (Fishman, 2004). In contrast, systemic blood pressure at high altitude is slightly lower than it is a sea level.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in systematic arterial pressure during acute exposure to high altitude, and the accompanying changes in blood pressure have been linked to increase in autonomic and sympathetic activity (Rhodes et al, 2011). The exposure of the lung at high altitude decreases inspired oxygen, thereby triggering hypoxic pulmonary vasoconstriction reflex (Fishman, 2004). Prolonged exposure hypoxia might result to sustain elevated arterial BP and diastolic BP (Hoit, Dalton, Gebremedin, Janocha, Zimmerman, & Zimmerman, 2011;Wolfel, Selland, Mazzeo, & Reeves, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged exposure hypoxia might result to sustain elevated arterial BP and diastolic BP (Hoit, Dalton, Gebremedin, Janocha, Zimmerman, & Zimmerman, 2011;Wolfel, Selland, Mazzeo, & Reeves, 1994). However, arterial BP remains normal by enhanced vascularization attributable to decreased total peripheral resistance in adults residing in mountainous regions (Fishman, 2004;Pocock & Richards, 1999). Again, other studies have reported that inhabitants of high altitude exhibits lower systolic and diastolic BP readings compared to low altitude population (Hoit, Dalton, Gebremedin, Janocha, Zimmerman, & Zimmerman, 2011;Hanna, 1999;Shrestha, Shrestha, Shrestha, & Bhattarai, 2012;Tripathy & Gupta, 2007).…”
Section: Introductionmentioning
confidence: 99%